2004
DOI: 10.1128/jb.186.14.4620-4627.2004
|View full text |Cite
|
Sign up to set email alerts
|

First Characterization of an Archaeal GTP-Dependent Phosphoenolpyruvate Carboxykinase from the Hyperthermophilic Archaeon Thermococcus kodakaraensis KOD1

Abstract: Phosphoenolpyruvate carboxykinase (PCK), which catalyzes the nucleotide-dependent, reversible decarboxylation of oxaloacetate to yield phosphoenolpyruvate and CO 2 , is one of the important enzymes in the interconversion between C 3 and C 4 metabolites. This study focused on the first characterization of the enzymatic properties and expression profile of an archaeal PCK from the hyperthermophilic archaeon Thermococcus kodakaraensis (Pck Tk ). Pck Tk showed 30 to 35% identities to GTP-dependent PCKs from mammal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 32 publications
(29 reference statements)
3
44
0
Order By: Relevance
“…The absorbance change at 340 nm was monitored for 10 min. Phosphoenolpyruvate carboxykinase (PEPCK; EC 4.1.1.32) activity was determined under aerobic conditions by the method of Fukuda et al (2004) using 50 mM NaHCO 3 , 5 mM MnCl 2 , 10 mM phosphoenolpyruvate (PEP), and 2 mM GDP in 100 mM imidazole buffer (pH 7.2). The reaction was started by addition of protein and incubated at 37 uC for 30 min, stopped by addition of 50 mM EDTA and cooled to 4 uC.…”
mentioning
confidence: 99%
“…The absorbance change at 340 nm was monitored for 10 min. Phosphoenolpyruvate carboxykinase (PEPCK; EC 4.1.1.32) activity was determined under aerobic conditions by the method of Fukuda et al (2004) using 50 mM NaHCO 3 , 5 mM MnCl 2 , 10 mM phosphoenolpyruvate (PEP), and 2 mM GDP in 100 mM imidazole buffer (pH 7.2). The reaction was started by addition of protein and incubated at 37 uC for 30 min, stopped by addition of 50 mM EDTA and cooled to 4 uC.…”
mentioning
confidence: 99%
“…There was no obvious difference in the signal intensities under all conditions examined, indicating constitutive transcription without regulation depending on the carbon source. This profile is significantly different from that of Tk-pck, of which transcription was induced under gluconeogenic conditions (Fukuda et al 2004). We further noticed that the transcription of Tk-mae appeared to be much weaker than that of Tk-pck.…”
Section: Expression Profile Of Tk-maementioning
confidence: 75%
“…The genome analysis also revealed that the TCA cycle is incomplete because of the absence of enzymes for many reactions. We have recently reported the first characterization and expression profile of an archaeal PCK from T. kodakaraensis (Tk-Pck) (Fukuda et al 2004). The characteristics of the recombinant protein and expression profile of Tk-Pck were consistent with a role in providing PEP from OAA as the first step of gluconeogenesis.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…ATP-PEPCKs are mainly present in bacteria, yeast, and plants, whereas GTP-PEPCKs are mostly present in higher eukaryotes, archaea, and some bacteria (21). PEP carboxylase exists in various bacteria and in limited archaea and eukaryotes.…”
Section: Reactions 4 Andmentioning
confidence: 99%